Restrictive mitral valve annuloplasty for chronic ischaemic mitral regurgitation: outcomes of flexible versus semi-rigid rings - Pang, Philip Y. K. (J Thorac Dis, 2019)
BACKGROUND: Restrictive mitral annuloplasty is the mainstay of surgical correction of chronic ischaemic mitral regurgitation (CIMR). Long-term data on the various types of annuloplasty rings is limited. The aim of this study was to investigate the clinical and echocardiographic outcomes of restrictive mitral annuloplasty in patients with CIMR, comparing the use of flexible versus semi-rigid annuloplasty rings. METHODS: A retrospective review was conducted for 133 patients with CIMR who underwent restrictive mitral annuloplasty at our institution between 1999 and 2015. Patient demographics and postoperative outcomes were analyzed. RESULTS: Mean age was 61.9±9.2 years and 103 patients (77.4%) were male. All patients underwent coronary artery bypass grafting, with a mean of 3.3±0.8 grafts. Flexible rings was implanted in 39 patients (29.3%, group F) and semi-rigid rings in 94 (70.7%, group R). Preoperative New York Heart Association class was III/IV in 104 patients (78.2%). Mean preoperative left ventricular ejection fraction was 28.8%±10.2%. Preoperative mitral regurgitation was moderate in 51 patients (38.3%) and severe in 82 (61.7%). In-hospital mortality occurred in 11 patients (8.3%). Overall survival at 1, 5 and 10 years were, respectively, 86.4%, 69.7% and 45.9%. At 10 years, overall survival (group F 53.1%, group R 40.0%, P=0.330) and freedom from moderate to severe MR (group F 53.1%, group R 53.8%, P=0.725) did not differ significantly. Freedom from hospitalization for heart failure was 59.3%. Left ventricular reverse remodelling, defined as a reduction of left ventricular end-systolic volume index >15%, occurred more commonly in Group R (51.1%) compared to Group F (23.1%), P=0.003. CONCLUSIONS: Restrictive mitral annuloplasty was associated with an operative mortality of 8.3%. Heart failure symptoms and significant MR recur in approximately 40% of patients after 10 years. Survival remained suboptimal and was not influenced by the type of annuloplasty ring.